Resolvemos situaciones problemticas con porcentaje - Bautista Cerna, Rosario Amparo (2018)
This report shows the development of mathematical skills applying sociocognitive paradigms: humanists who develop capacities through activities consisting of skills, techniques, methods, contents and attitudes that allow applying their new knowledge to everyday situations. The session entitled solves problematic situations with percentage, was developed in the area of mathematics taking into account the competence Solves Quantity problem, the performance of Translate relationships between data and actions to compare and equalize quantities with percentage was achieved, when posing and solving problems. During our daily experience we face various economic, financial, buying and selling situations; in which percentage is involved and for this we must be prepared to interpret and implement it properly. In the development of the session, motivational activities were applied in a cognitive and challenging way that encouraged the achievement of mathematical competence and abilities; The pedagogical processes such as motivation, exploration of previous knowledge, problematization, management and accompaniment and evaluation were taken into account; understanding of the problem and transfer in the didactic processes. The active and constant participation of students was promoted individually and collaboratively, thus showing their new learning and transferring it to similar situations.